Differentiation Efficiency of Induced Pluripotent Stem Cells Depends on the Number of Reprogramming Factors123. (14th February 2012) - Löhle, Matthias; Hermann, Andreas; Glaß, Hannes; Kempe, Andrea; Schwarz, Sigrid C.; Kim, Jeong Beom; Poulet, Claire; Ravens, Ursula; Schwarz, Johannes; Schöler, Hans R.; Storch, Alexander
Abstract: Reprogramming of somatic cells into induced pluripotent stem cells (iPSCs) by retroviral overexpression of the transcription factors Oct4, Sox2, Klf4, and c‐Myc holds great promise for the development of personalized cell replacement therapies. In an attempt to minimize the risk for chromosomal disruption and to simplify reprogramming, several studies demonstrated that a reduced set of reprogramming factors is sufficient to generate iPSC, albeit at lower efficiency. To elucidate the influence of factor reduction on subsequent differentiation, we compared the efficiency of neuronal differentiation in iPSC generated from postnatal murine neural stem cells with either one (Oct4; iPSC1F‐NSC ), two (Oct4, Klf4; iPSC2F‐NSC ), or all four factors (iPSC4F‐NSC ) with those of embryonic stem cells (ESCs) and iPSC produced from fibroblasts with all four factors (iPSC4F‐MEF ). After 2 weeks of coculture with PA6 stromal cells, neuronal differentiation of iPSC1F‐NSC and iPSC2F‐NSC was less efficient compared with iPSC4F‐NSC and ESC, yielding lower proportions of colonies that stained positive for early and late neuronal markers. Electrophysiological analyses after 4 weeks of differentiation identified functional maturity in neurons differentiated from ESC, iPSC2F‐NSC, iPSC4F‐NSC, and iPSC4F‐MEF but not in those from iPSC1F‐NSC . Similar results were obtained after hematoendothelial differentiation on OP9 bone marrow stromal cells, where factor‐reduced iPSC generated lower proportions of colonies with hematoendothelial progenitors than colonies of ESC, iPSC4F‐NSC, and iPSC4F‐MEF . We conclude that a reduction of reprogramming factors does not only reduce reprogramming efficiency but may also worsen subsequent differentiation and hinder future application of iPSC in cell replacement therapies. STEM CELLS 2012;30:570–579